Effectiveness of Digital Nudging Promoting Pro-Environmental Behavior - Silvennoinen, Mari (2025)
As environmental crises continue to worsen, shifting individual behavior toward sustainability has become increasingly important. Addressing these environmental challenges requires not only systemic changes but also alterations in everyday behaviors. Traditional interventions often demand substantial resources and have had mixed success. In contrast, digital nudging — subtle interventions within digital environments — offers a promising alternative to influence behavior without restricting personal choice. However, evidence regarding its effectiveness in promoting pro-environmental behavior (PEB) remains fragmented. This thesis aims to fill that gap by systematically investigating the effectiveness of digital nudges in promoting PEB across various domains. It also examines how different types of digital nudges compare to traditional nudging methods. Using an umbrella review methodology, this study synthesizes findings from recent systematic reviews and meta-analyses. Studies were selected through systematic database searches and analyzed by using qualitative synthesis. The results indicate that digital nudging can positively influence sustainable behavior, although its effectiveness varies based on the type of nudge, the target domain, and contextual factors. To maximize impact, systemic and multi-level approaches are essential. Additionally, the findings highlight gaps in long-term evidence and point to significant publication bias in existing research. This thesis provides practical recommendations for designing digital nudging interventions and outlines priorities for future research to enhance evidence-based strategies for sustainable behavior change.